Global perspectives on volunteerism: Analysing the role of the state, society and social capital. Issue 7 (11th July 2016) - Halsall, Jamie; Cook, Ian; Wankhade, Paresh
Abstract : Purpose: – The purpose of this paper is to examine the concept of volunteerism in three different case countries, namely, that of USA, UK and China while highlighting the role of the state, society and social capital. Design/methodology/approach: – The paper reviews the extant literature on the volunteering traditions in the chosen case study countries highlighting the idiosyncrasies while analysing implications for future research. Findings: – The paper highlights the role of the state, society and social capital in the chosen countries, each deriving its origins from the specific traditions in those countries. Research limitations/implications: – This paper provides a conceptual review focusing on the key literature in the field. The authors have examined various academic texts and published materials. Practical implications: – This paper provided an update critically discussion on the concept of volunteerism in three different case countries. Social implications: – This paper is highly relevant to academics and social policy makers. Moreover, this paper has been written from an international context. Originality/value: – The paper makes an original contribution by comparing and contrasting three important countries with different histories and traditions of volunteerism highlighting diversity of type and application.